The Effect of Education Earthquakes and Tsunami Preparadness Emergency Planning - Niken Setyaningrum; Deviayana Usmawati (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Background: Bantul regency.is one of the areas in which there is the danger of earthquakes and tsunamis. To minimize the impact disasters need to have knowledge on communities including elementary school students who are part of communities that are vulnerable to disasters. Objective: The purpose of this study was to understand the effects of earthquake and tsunami education on elementary school emergency planning Jigudan Pandak Bantul Yogyakarta. Research Methods: Quantitative precision using pre experimental methods. Approach used in one group pretest-posttest design. The population of this study was 46 students in 5 of grade of 10-12 years old. Sample taking used the total sample. The instrument used is a questionnaire. The statistical test for Wilcoxon. Emergency planning research before they gave education to earthquake and tsunami disasters total 15 responders (32.6%) ready, 22 reponders (47.8%) almost ready, 9 responders (19.6%) less ready. Research Results: Emergency planning after giving them earthquake and tsunami aducation total 35 responders (76.1%) completely ready, 11 responders (23.9%) ready. Statistical test using the Wilcoxon score (P: 0,00) was smaller than or equal to degrees of prospering α: 0.05 (p : 0,000 < 0,05 ). Conclusion: There was a significant impact on the readiness of emergency planning students before and after being given the education of earthquake and tsunami disasters. Keywords: Education Disaster Earthquake, Emergency Planning, Tsunami